PERAN PEMERINTAH INDONESIA DALAM MENGATASI PERILAKU LESBIAN TENAGA KERJA WANITA DI HONGKONG (2007-2009) - Nadiya Afifah; Pakpahan Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study examines the role of the indonesian government in dealing with thephenomenon of lesbian women in Hongkong workforce (2007-2009). This research is a greatstudy in International Relations which seeks to look at the role of government and the relationto the dynamics of migrant workers (TKI), particularly the behavior of TKW in Hongkong.Hongkong is a country that receives a lot of opportunities maids from Indonesia. With themultitude of TKW in Hongkong appear various problems either violence or harassment.There is one problem that arises within the maids in Hongkong which is a new phenomenonthat emerged quickly jumped in number from year to year which TKW relationship withfellow maids called